1995
DOI: 10.1093/ageing/24.3.247
|View full text |Cite
|
Sign up to set email alerts
|

Function of the Oxidative Metabolism of Phagocytes in Elderly People: Relationship to Nutritional and Inflammatory Status

Abstract: The purpose of this study was to investigate the phagocyte production of oxygen-free radicals (OFR) in the whole blood of elderly patients (EP), by measuring chemiluminescence at the basal state and after stimulation, and to study the relationships between its impairment, if any, and blood indices of the nutritional and inflammatory status in elderly patients with (Inf) and without (N-Inf) inflammatory diseases. The results showed that OFR production by resting circulating phagocytes, assessed by chemiluminesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Among other physiopathological phenomena linked to these modifications, there is an overproduction of free radicals leading to abnormalities of immune response and the sensitivity to infection. 8) The association between aging and diseases involving free radical reactions seems to be directly implicated in psychic and behavioral disorders. In contrast to other kinds of psychotropic drugs, nootropic or cognition enhancing drugs could be indicated.…”
Section: Resultsmentioning
confidence: 99%
“…Among other physiopathological phenomena linked to these modifications, there is an overproduction of free radicals leading to abnormalities of immune response and the sensitivity to infection. 8) The association between aging and diseases involving free radical reactions seems to be directly implicated in psychic and behavioral disorders. In contrast to other kinds of psychotropic drugs, nootropic or cognition enhancing drugs could be indicated.…”
Section: Resultsmentioning
confidence: 99%
“…linked an increase in IL-10 to neovascularisation, making age-related macular degeneration more aggressive ( 37 ). Alongside IL-10, overproduction of ROS appeared commonplace in ageing ( 78 , 79 ), which could lead to excess tissue and DNA damage through oxidative inflammatory stress ( 78 ), cytotoxicity and abnormal growth of cancer cells ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that, in old mice, the CLI of peritoneal cells, stimulated by zymosan or by fMetLeuPhe, were higher than those observed in young mice, and that, after stress, the macrophages of old mice did not increase their FOR production as did the macrophages of young mice. Studies in both elderly people (13) and old beagle dogs (30) have shown that blood peripheral phagocytes had both a considerably increased FOR production at the basal state, and a relatively impaired capacity of response to stimulating agents. Lavie (31) observed a significant age-dependent variation in the chemiluminescence response of mouse peritoneal macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The phagocytic system is the first line of defence that could be involved in the immune responses to stress. In humans, we have shown that overproduction of free oxygen radicals (FOR) can be a common response pathway of phagocytic cells to both stress and ageing, leading to abnormalities in other types of immune responses and to sensitivity to infections (13). On the other hand, failure of psychological defences, particularly depression, is more likely with ageing (14,15) and could add its own effects to those directly related to ageing (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%